The effect of omega-3 supplementation on serum levels of YKL-40, BMP-4, and ox-LDL in men with coronary artery disease: a randomized double-blind placebo-controlled trial - Samavat, Simin; Javanbakht, Mohammad Hassan; Nematipour, Ebrahim; Zareei, Mahnaz; Mohammadzadeh Honarvar, Niyaz; Ramezani, Atena; Mohammadi, Hamed; Djalalli, Mahmoud (Progress in Nutrition, 2019)
Objective: Bone morphogenic protein-4 (BMP-4), oxidized low density lipoprotein (ox-LDL), and YKL-40 are the potential biomarkers which may causes inflammation and cardiovascular disease. Omega-3 fatty acid-rich diets may have anti-inflammatory effects. This study was designed to determine the effects of omega-3 fatty acid supplementation on serum YKL-40, BMP-4, and ox-LDL levels in men with coronary artery disease (CAD). Methods: The current study was a randomized, placebo-controlled, double-blind parallel-group clinical trial that involved 42 male patients with CAD. The volunteers were randomly allocated into two groups to receive 4 g omega-3 (containing 720 mg EPA plus 480 mg DHA) supplements (n = 21) or placebo (n = 21) per day for 8 weeks. Fasting blood samples were taken at the beginning and end of the trial to quantify serum levels of ox-LDL, YKL-40 and BMP-4 concentrations. Result: The results identified that omega-3 fatty acid supplementation for 8 weeks had a noticeable effect on serum ox-LDL (P = 0.03), YKL-40 (P = 0.01), and BMP-4 (P = 0.01) concentrations between groups. A significant difference was found between placebo and omega-3 supplementation groups only for BMP-4 (P = 0.046) after removing counfounding effects of vitamin C and carbohydrates. Conclusions: The results of this study indicate that omega-3 supplementation decreased serum BMP-4 significantly. Serum YKL-40 correlated with ox-LDL before intervention. Further study is recommended to elucidate the exact mechanisms for this process.